2013
DOI: 10.7314/apjcp.2013.14.1.347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allogeneic Blood Transfusion in Patients with Stage II Colon Cancer

Abstract: The aim of the present study was to determine whether allogeneic red blood cell transfusions showed a deleterious effect and what might be preoperative risk factors for blood transfusion in patients with TNM stage II colon cancer. Total 470 patients who fulfilled inclusion criteria were selected for a further 10-year followup study. We found that there were statistical significance between non-transfused and transfused group in mortality (P=0.018), local recurrence (P=0.000) and distant metastasis (P=0.040). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Recent studies had demonstrated that peri-operative allogeneic blood transfusion had an adverse effect on patients with surgical intervention in various malignancies (Liu et al, 2013;Meng et al, 2013;Ramos et al, 2003;Sugita et al, 2008;Wang et al, 2015). Some of these investigations further indicated that peri-operative transfusion of RBC product, rather than post-operative, was highly associated with prolonged hospital stay as well as increased morbidity and mortality (Ramos et al, 2003;Sugita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had demonstrated that peri-operative allogeneic blood transfusion had an adverse effect on patients with surgical intervention in various malignancies (Liu et al, 2013;Meng et al, 2013;Ramos et al, 2003;Sugita et al, 2008;Wang et al, 2015). Some of these investigations further indicated that peri-operative transfusion of RBC product, rather than post-operative, was highly associated with prolonged hospital stay as well as increased morbidity and mortality (Ramos et al, 2003;Sugita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intra-operative blood transfusion is an indispensible complementary therapy due to the large traumas, longer duration and more hemorrhage volume in the operations for cancer patients, which can immediately remedy the intraoperative anemia and insufficient blood volume. However, blood transfusion-associated immunosuppression may further aggravate the postoperative immunosuppression of cancer patients, which will enable residual and exfoliative tumor cells escape from immunological surveillance, leading to recurrence and distant metastasis of tumors (De Oliveira et al, 2012;Meng et al, 2013). A study found that autologous blood transfusion could improve the postoperative immunological function and protect organs of cancer patients (Han et al, 2011;Stachura et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence in the literature that blood transfusion may have a negative impact on the progression of disease. Meng J had demonstreated that allogeneic blood transfusion increased the postoperative tumor mortality, local recurrence and distant metastasis in patients with colon cancer ( Meng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%